IMPLEMENTASI ENTERPRISE RESOURCE PLANNING (ERP) BERBASIS SYSTEM APPLICATION AND PRODUCT (SAP): STUDI KASUS PERUM JASA TIRTA 1 - Alycia, Fiorenza; Ramadhina Indah Audeskin; Shilla Fatonah; Nayla Alya Putr; Aryan Danil Mirza BR (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2025)
Perum Jasa Tirta I as a state-owned enterprise engaged in water resources management, faces challenges in integrating various business processes and improving operational efficiency. The implementation of an Enterprise Resource Planning (ERP) system based on System Application and Product (SAP) was chosen as a solution to overcome these challenges and support the company's digital transformation. This research uses a qualitative approach through literature study analysis and secondary data. Data collection is done through tracing the company's annual report and interviews with related parties at Perum Jasa Tirta I to understand the implementation of accounting information systems based on SAP. The implementation of SAP at Perum Jasa Tirta I includes several main modules such as Financial Accounting, Controlling, Sales and Distribution, Material Management, and Human Capital Management. This implementation resulted in improved operational efficiency, data accuracy, transparency, and reporting quality. However, the company also faced challenges such as system complexity, customization needs, high implementation costs, and change management. In conclusion, the use of System Application and Product (SAP) as an Accounting Information System at Perum Jasa Tirta I has had a significant positive impact on the operational efficiency and accuracy of the company's financial reporting, although there are some challenges.